Teaching information literacy in the humanities: Engaging students with primary sources and cultural heritage material - Pettersson, Karin (Nordic Journal of Information Literacy in Higher Education, 2022)
Many university libraries hold large cultural heritage collections that are unknown to most students. The digitisation of these collections offers new ways of working with primary sources, and with it, an increased interest in archives and older collections, both in digital and physical form. This article discusses how archival material and other primary sources can be used in our information literacy classes, thus broadening the understanding of information literacy to include primary source literacy. I share two examples of how my colleagues and I have engaged students with primary sources and discuss the pedagogical challenges and opportunities. The article also addresses the disciplinary aspect of information literacy and what a humanities approach to teaching information literacy could incorporate. Drawing on own experiences and previous research, the article concludes that using primary sources in information literacy classes can enrich learning, engage students, and develop our teaching practices.